Corruption and Economic Development in the SADC Region: A Nonlinear Panel ARDL Approach - Mafeta, Lehlohonolo Godfrey; Niyimbanira, Ferdinand (International Journal of Economics and Financial Issues, 2025)
Many African nations, particularly those within the Southern African Development Community (SADC), face significant challenges due to pervasive corruption. The impact of corruption on economic wellbeing has been scrutinised for years, with its impact ranging from economic growth and development, foreign direct investment, its impact on living standards, service delivery, and poverty levels. The existing literature presents two contrasting views: the “sand the wheels” hypothesis, which posits that corruption hampers economic development, and the “grease the wheels” hypothesis, which argues the opposite. This study seeks to determine the asymmetric impact of corruption on economic development and to model a corruption threshold that has a non-detrimental impact on economic development. Employing a nonlinear panel autoregressive distributed lag model and a panel threshold model. The study reveals that changes in corruption levels have influence on economic development, with reductions in corruption being particularly more beneficial. The findings suggest that corruption impedes development, especially when corruption levels are below a threshold of 0.64, measured by control of corruption indicators, and 41 on the corruption perception index. The results underscore the necessity of concerted efforts to combat corruption to foster improved economic development in SADC countries. This study outlines several policies for eradicating corruption.